EFFECT OF DIFFERENT SOURCES OF LIGHT AS NIGHT BREAK ON GROWTH AND FLOWERING OF KOREAN CHRYSANTHEMUM (Chrysanthemum morifolium Chrysanthemum morifolium Chrysanthemum morifolium Ramat.) GENOTYPES - RANJIT SINGH; MADHU BALA (The Bioscan, 2018)
Korean chrysanthemum occupies the prominent position in world trade of cut flowers. As chrysanthemum is classified as short-day plant, flower bud initiation is highly controlled by prevailing photoperiods which have marked influence on flower production. Extended photoperiods are generally provided to delay flower bud initiation as Night Break (NB) treatment instead of continuous lighting to save energy. The present study was aimed to compare the effect of three (Incandescent bulbs, Compact fluorescent lights and light emitting diodesLED) sources of light as NB treatment on ten genotypes of chrysanthemum belonging to Korean group. The night break treatment with LED lights resulted in increased plant height (66.85 and 67.76 cm) and plant spread (25.73 and 26.65cm) during 2015 and 2016 respectively. The Flowering was significantly delayed (148.34 and 149.25 days) under the NB induced by LED lights as compared to other two sources of light used for the study. Internodal length was recorded maximum (8.20 and 9.00 mm) under LED lights. Similar trends were recorded for number of flowers per plant, flower size and vase life. However, none of the source of light could affect significantly the number of branches per plant. Different genotypes showed varied response towards NB treatment as the flower bud appearance was recorded earliest (136.93 and 137.89 days) in Yellow Delight while in Punjab Shyamli it was significantly delayed (193.57 and 193.48 days). It is thus concluded that LED lights are more effective when intending to photoperiodic delay of the flowering in Korean chrysanthemum compared to other sources of light